If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 + 3x = 24 Solving 9 + 3x = 24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 24 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 24 + -9 3x = 24 + -9 Combine like terms: 24 + -9 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| 6(8)-6=54 | | 3x+2x-1=9 | | 6x-y=54 | | 6+4x=26 | | 8+3x=41 | | 5+5x=45 | | 2+7x=51 | | 4x-2=5x-8 | | x^2+3x+9= | | 5+2x=21 | | 9+7x+4x=31 | | 4k=3(k+2)-2k | | 5x+6+5x=106 | | 2n-2+4n=6n-1 | | 10+6x+4x=100 | | 2(3x+17)=4 | | 6x+1+2x=49 | | x^3+x^2-10x+8=0 | | 6+2x+3x=6 | | 15=x+5x+3 | | 2.5x+1.3x= | | -11+7n-21=25 | | 7x+1+6x=157 | | 35x+155=589-89x | | 9+7x+3x=79 | | -5x+3.2=-3x+3.6 | | 6x^2+4x-40= | | -9x+3.1=5x-9.5 | | 29=x+3x+9 | | 7x+2.0=-4x+9.7 | | 6x+10+5x=43 | | 9n-22=59 |